Utilizing DICOM data to generate custom computer-aided designing and computer-aided machining polyetheretherketone healing abutments for an ear prosthesis - Mohit Dhiman; Sudhir Bhandari; Sunil Gaba (Wolters Kluwer Medknow Publications, 2020)
Soft tissue healing around implants may turn out to be the most decisive factor in the success or failure of the prosthesis. Dimension, configuration, and material of the healing abutments play a pivotal role in achieving optimal soft tissue architecture around implants. Digital imaging with computer-aided designing and computer-aided machining (CAD-CAM) technology, has made it easier to illustrate, design, replicate maxillofacial structures, and generate its supporting elements in a reliable, faster, and more convenient manner. This case report highlights the issue relevant to the implant-supported prosthetic replacement, on a site previously attempted for surgical reconstruction of the missing ear. Presurgical DICOM data were used to obtain custom CAD-CAM polyetheretherketone (PEEK) healing abutments on implants in a patient with an excessive amount of tissue in the missing right ear region. It is probably the first extraoral use of PEEK as a healing abutment in the workflow of implant retained maxillofacial prosthetics. No issue warranting the removal of the PEEK component was observed during the duration of its use.